2013
DOI: 10.2133/dmpk.dmpk-12-rg-128
|View full text |Cite
|
Sign up to set email alerts
|

Role of Methotrexate Polyglutamation and Reduced Folate Carrier 1 (RFC1) Gene Polymorphisms in Clinical Assessment Indexes

Abstract: The aims of the present study were to define inter-individual differences in response to methotrexate (MTX) through MTX polyglutamate (MTX-PG) levels in red blood cells (RBC) and MTX-related gene polymorphisms. A total of 145 rheumatoid arthritis patients were recruited. MTX-PG1-5 concentrations in RBC were measured, and 11 single nucleotide polymorphisms, all in MTX-related genes involved in the folate pathway, were analyzed. Disease activity was also assessed. There was no direct relationship between any MTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
9
1
1
Order By: Relevance
“…According to non‐clinical studies, higher polymerization in MTX‐PGs led to stronger enzyme‐inhibiting activities 14‐16 . However, according to some previous reports of clinical analysis data, the treatment effects of MTX were correlated with total concentrations of MTX‐PGs, 17‐22 whereas the correlation between total MTX‐PG concentrations and effectiveness was not clear in other reports 23,24 . In this study, there was no considerable difference in the increase of MTX‐PG 2–5 concentrations between dose regimens.…”
Section: Discussioncontrasting
confidence: 59%
“…According to non‐clinical studies, higher polymerization in MTX‐PGs led to stronger enzyme‐inhibiting activities 14‐16 . However, according to some previous reports of clinical analysis data, the treatment effects of MTX were correlated with total concentrations of MTX‐PGs, 17‐22 whereas the correlation between total MTX‐PG concentrations and effectiveness was not clear in other reports 23,24 . In this study, there was no considerable difference in the increase of MTX‐PG 2–5 concentrations between dose regimens.…”
Section: Discussioncontrasting
confidence: 59%
“…Wang et al 34 concluded that RFC1 80 homozygote AA was significantly associated with increased risk of esophageal cancer in a Chinese population. Ando et al 35 observed that the level of PGMTX (PG-5) in red blood cells was lower in rheumatoid arthritis with 80 A allele. The common feature in these studies appears to be that the lower the concentration or retention of PGMTX in tumor cells is, the less the efficacy of the MTX and worse patient response.…”
Section: Discussionmentioning
confidence: 99%
“…As a transporter of folacin, RFC1 plays a critical role in membrane transport of MXT and its metabolites. RFC1 participates in regulating cellular uptake of MTX and cellular efflux of MTX‐PGs . RFC1 G80A impairs transporting of MTX into cells caused a lower level of MTX .…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular MTX is converted to more active MTX‐PGs with up to seven glutamyl residues (MTX‐PG 1 to MTX‐PG 7 ). Longer chain polyglutamates have longer antifolate effects, with better retained in cells . Dervieux et al concluded that there was a higher level of intracellular MTX‐PG 5 in patients with RFC1 80AA genotype .…”
Section: Discussionmentioning
confidence: 99%